2017
DOI: 10.21873/anticanres.11886
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Iron Chelators ATA and DFO on MCF-7 Breast Cancer Cells and Phosphatases PTP1B and SHP2

Abstract: We confirmed that iron chelating can be considered as a potential strategy for the adjunctive treatment of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…34,37,38 The observation that iron chelation precipitates timedependent detrimental effects against nonmetastatic (MCF-7) and metastatic (MDA-MB-231) breast cancer cells (Figures 6 and 7) is consistent with previous reports which have shown that DFO treatment minimizes cell migration and wound healing potential in MCF-7 cells 34 and that it decreases the viability and proliferation of breast cancer cells. 43 This is in agreement with the observation that DFO-induced LIP depletion increases the susceptibility of cell lines like K562 to doxorubicin 38 and that DFO treatment in TP53-MDA-MB-231 and TP53-MCF-7 results in pronounced epigenetic alterations that associate with increased apoptosis and enhanced sensitivity to doxorubicin and cisplatin. 44 Increased expression of g-H2AX and decreased expression of surviving with increasing concentration of DFO as shown in Figure 6 further confirm the apoptotic potential of iron chelation.…”
Section: Discussionsupporting
confidence: 89%
“…34,37,38 The observation that iron chelation precipitates timedependent detrimental effects against nonmetastatic (MCF-7) and metastatic (MDA-MB-231) breast cancer cells (Figures 6 and 7) is consistent with previous reports which have shown that DFO treatment minimizes cell migration and wound healing potential in MCF-7 cells 34 and that it decreases the viability and proliferation of breast cancer cells. 43 This is in agreement with the observation that DFO-induced LIP depletion increases the susceptibility of cell lines like K562 to doxorubicin 38 and that DFO treatment in TP53-MDA-MB-231 and TP53-MCF-7 results in pronounced epigenetic alterations that associate with increased apoptosis and enhanced sensitivity to doxorubicin and cisplatin. 44 Increased expression of g-H2AX and decreased expression of surviving with increasing concentration of DFO as shown in Figure 6 further confirm the apoptotic potential of iron chelation.…”
Section: Discussionsupporting
confidence: 89%
“…Preclinical models showed variable uptake of fluorescently-labeled transferrin at metastatic sites. Treatment with DFO [ 30 , 76 ] increased the uptake of transferrin conjugates by breast cancer cells in vitro and in a mouse model of metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4, even a slight change in the structure of the inhibitory compound may lead to a lower inhibitory effect (44)(45)(46). Such correlation was obsevered related to aurintricarboxylic acid (ATA) which reveals high inhibitory effect on PTP1B (47). However, the experiments conducted on other tyrosine phosphatase YopH has shown that the analogs of ATA are weaker inhibitors than their precursor (48).…”
Section: Promising Inhibitors Of Protein Tyrosine Phosphatase Ptp1bmentioning
confidence: 99%